Updating intensity–duration–frequency curves for urban infrastructure design under a changing environment. (1st March 2021) - Yan, Lei; Xiong, Lihua; Jiang, Cong; Zhang, Mengjie; Wang, Dong; Xu, Chong‐Yu
Abstract: The intensity and frequency of extreme precipitation have increased in many regions in the past century due to climate change. Many studies have revealed that short‐duration extreme precipitations are likely to become more and more severe in many areas, thus raising a question on whether our urban infrastructures have been designed adequately to cope with these changes. Currently, Intensity–duration–frequency (IDF) curves, which summarize the relationships between the intensity and frequency of extreme precipitation for different durations, are recommended as a criterion for urban infrastructure design and stormwater management. However, climate change is thought to have invalidated the stationary assumption in deriving IDF curves, that is, current IDF curves could misevaluate future extreme precipitation in many cases. Therefore, it is necessary to update the current IDF curves by considering possible changes of extreme precipitation. In this review, we first summarize observed changes in urban short‐duration extreme precipitation and explore the physical mechanisms associated with changes. Then, we introduce two major approaches for updating IDF curves, namely the covariate‐based nonstationary IDF curves and climate‐model‐based IDF curves. Advances in these two updating approaches for IDF curves are the focus of this review. These include the investigation of physically‐based covariates with nonstationary modeling of extreme precipitation; nonstationary precipitation design strategies; and the statistical downscaling and dynamic downscaling methods for projecting future short‐duration precipitation. Finally, we summarize some future research challenges and opportunities on providing reliable projections of future short‐duration extreme precipitation and better characterize the probabilistic behavior of short‐duration extreme precipitation for IDF design. This article is categorized under: Engineering Water > Engineering Water Abstract : Schematic diagram of updating current stationary IDF curves under changing environment.